2019
DOI: 10.3855/jidc.11657
|View full text |Cite
|
Sign up to set email alerts
|

Threshold value of the anti-HCV test in the diagnosis of HCV infection

Abstract: Introduction: In the diagnosis of hepatitis C virus (HCV) infection, the first step is screening for anti-HCV antibodies, and positive results are generally confirmed with nucleic acid amplification tests. Recent studies have reported that more compatible results have been obtained with the HCV RNA test using signal to cut-off (S/Co) values >1, which are the routine reactivity threshold for the anti-HCV enzyme immunoassay (EIA) test. The aim of this study was to determine the most appropriate S/Co value for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
3
6
2
Order By: Relevance
“…In our study, 70.2% of the patients were found to have a false positive result. In a study by Kirisci et al in Turkey, the false positivity rate was found to be 61%, which was close to the rates in our study (12). The false positivity rates were found to be 58% and 48.9% in the studies conducted by Aydın et al and Moorman et al, respectively (13,14).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, 70.2% of the patients were found to have a false positive result. In a study by Kirisci et al in Turkey, the false positivity rate was found to be 61%, which was close to the rates in our study (12). The false positivity rates were found to be 58% and 48.9% in the studies conducted by Aydın et al and Moorman et al, respectively (13,14).…”
Section: Discussionsupporting
confidence: 89%
“…The anti-HCV antibody value, age, and gender are the first three correlations given, as presented in Table 1. According to [17], the diagnostic threshold for determined the most appropriate value to be 12.27.…”
Section: Resultsmentioning
confidence: 99%
“…Optimal values for anti-HCV S/Co varies in different studies. It was determined as 2.7 in the study by Sharifi et al [13], 5 in the study by Şanlıdağ et al [14], 7.13 in the study by Gülden et al [15], 10.9 in the study by Seo et al [16], 12.27 in the study by Kirişçi et al [17], 26 in the study by Sookoyan et al [18] and 25.9 in the study by Balk et al [19]. In terms of epidemiology, if the prevalence of a disease in a population is low, the false positive rate increases and the positive predictive value (PPV), which provides the estimation of the true positivity of the test, decreases.…”
Section: Discussionmentioning
confidence: 96%